Response of the COPD Assessment Test to pulmonary rehabilitation in unselected chronic respiratory disease. Issue 6 (25th July 2013) - Kon, Samantha S.C.; Clark, Amy L.; Dilaver, Deniz; Canavan, Jane L.; Patel, Mehul S.; Polkey, Michael I.; Man, William D.‐C.
Abstract Background and objective The COPD Assessment Test (CAT) is a recently introduced, simple‐to‐use health status instrument that takes less time to complete than better‐established health status instruments. In chronic obstructive pulmonary disease (COPD) patients, the CAT improves with pulmonary rehabilitation (PR), and changes correlate with improvements in longer‐established health status instruments such as the Chronic Respiratory Questionnaire (CRQ). Increasing numbers of non‐COPD patients are referred for PR, but it is not known whether the CAT is responsive to PR in these populations. Methods The CAT score was prospectively measured in 365 consecutive patients (255 COPD, 110 non‐COPD) before and after an 8‐week PR programme. Pre to post change in CAT was calculated for COPD and non‐COPD patients, and correlated with change in the CRQ. Results For both non‐COPD and COPD patients, there was a similar and significant improvement in the mean (95% confidence interval) CAT score following PR (non‐COPD: −2.1 (−1.0, −3.2) vs COPD: −3.0 (−2.2, −3.8); P = 0.19). Change in CAT was significantly correlated with all domains of the CRQ in non‐COPD patients (all P < 0.01). Conclusions As in COPD patients, the CAT is immediately responsive to PR in non‐COPD patients. Even in unselected chronic respiratory disease patients undergoing PR, the CAT is a practical alternative to longer‐established health status questionnaires.